Enhancing academic skills appointments through a new booking system - Laurence Morris (Association for Learning Development in Higher Education (ALDinHE), 2020)
This case study examines the introduction of a centrally managed booking system for academic skills appointments conducted by the Library Academic Support Team at Leeds Beckett University, showing how staff-student communication channels can scaffold effective student support. The new system was introduced in order to manage a large number of requests for skills appointments across all academic levels, to ensure an equitable experience for all learners, and to frame staff-student encounters more effectively at the formative stage. Further benefits included provision of more focused tuition, additional data on learner requirements, greater capacity to re-route appointment requests, and more efficient use of student and staff time, while retaining the option of human intervention in the system as required. This paper demonstrates a transferrable means of enhancing institutional processes whilst retaining the traditional strengths of one-to-one encounters in order to improve the overall student experience.